Mapping stakeholders and policies in response to deliberate biological events - Katz, Rebecca (Heliyon, 2018)
BACKGROUND: Recent infectious disease outbreaks have brought increased attention to the need to strengthen global capacity to prevent, detect, and respond to natural biological threats. However, deliberate biological events also represent a significant global threat, but have received relatively little attention. While the Biological Weapons Convention provides a foundation for the response to deliberate biological events, the political mechanisms to respond to and recover from such an event are poorly defined. METHODS: We performed an analysis of the epidemiological timeline, the international policies triggered as a notional deliberate biological event unfolds, and the corresponding stakeholders and mandates assigned by each policy. FINDINGS: The results of this analysis identify a significant gap in both policy and stakeholder mandates: there is no single policy nor stakeholder mandate for leading and coordinating response activities associated with a deliberate biological event. These results were visualized using an open source web-based tool published at https://dbe.talusanalytics.com. INTERPRETATION: While there are organizations and stakeholders responsible for leading security or public health response, these roles are non-overlapping and are led by organizations not with limited interaction outside such events. The lack of mandates highlights a gap in the mechanisms available to coordinate response and a gap in guidance for managing the response. The results of the analysis corroborate anecdotal evidence from stakeholder meetings and highlight a critical need and gap in deliberate biological response policy.